Trypanites and associated bivalve borings in an Upper Albian hardground from the Eastern Saharan Atlas (Algeria). Issue 5 (October 2021) - Naimi, Mohammed Nadir; Vinn, Olev; Cherif, Amine; Benyoucef, Madani
Abstract: Abundant Trypanites isp. associated with Gastrochaenolites isp. and Petroxestes pera are evidenced in the first found hardground of the late Albian marine transgressive series, overlying the Continental Intercalaire in the Ouled Nail Range, eastern Saharan Atlas. This hardground is encrusted by oyster shells belonging to Ostrea falco Coquand. The studied hardground developed in warm environment and displays a lateral extension of at least 6 km. It is interpreted as an erosional transgressive surface. The ichnogenus Petroxestes is reported for the first time from Africa. This ichnoassemblage is attributed to the Trypanites ichnofacies.